2018
DOI: 10.1007/s00247-018-4197-6
|View full text |Cite
|
Sign up to set email alerts
|

Significance of pleural effusion at diagnosis in pediatric Hodgkin lymphoma: a report from Children’s Oncology Group protocol AHOD0031

Abstract: BackgroundPleural effusion at presentation in Hodgkin lymphoma has been associated with inferior outcome but has not been systematically evaluated.ObjectiveTo determine whether pleural effusion at presentation in children with Hodgkin lymphoma is a primary indicator of poor prognosis or secondary to associated factors.Materials and methodsChildren’s Oncology Group (COG) AHOD0031, a randomized, response-based, centrally reviewed protocol, enrolled 1,712 eligible patients <22 years of age with initial presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…The frequency of effusion lymphomas occurring concurrently at initial disease presentation varies in different series, ranging from 11.7% to 15.0% for pediatric newly diagnosed CHL, 10,12 to 30.0% of newly diagnosed DLBCL, 11 and 71.4% of lymphoblastic lymphoma 12 . Large mediastinal lymphadenopathy, higher serum levels of lactate dehydrogenase (LDH) and serum β‐2 microglobulin were reported to be associated with a higher incidence of effusion lymphomas 10,11 . In a study of 90 pediatric patients with acute lymphoblastic leukemia from Turkey, 26% (23 cases) had malignant pericardial effusions, including 74% B‐ and 26% T‐lineage neoplasms, respectively 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of effusion lymphomas occurring concurrently at initial disease presentation varies in different series, ranging from 11.7% to 15.0% for pediatric newly diagnosed CHL, 10,12 to 30.0% of newly diagnosed DLBCL, 11 and 71.4% of lymphoblastic lymphoma 12 . Large mediastinal lymphadenopathy, higher serum levels of lactate dehydrogenase (LDH) and serum β‐2 microglobulin were reported to be associated with a higher incidence of effusion lymphomas 10,11 . In a study of 90 pediatric patients with acute lymphoblastic leukemia from Turkey, 26% (23 cases) had malignant pericardial effusions, including 74% B‐ and 26% T‐lineage neoplasms, respectively 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Around 10% to 15% cases of malignant PE are caused by hematologic malignancy 5‐7 . Both Hodgkin and non‐Hodgkin lymphoma may cause malignant effusion, either as initial presentation or at disease progression/relapse 2,8‐13 . The relative frequencies of lymphoma types in malignant effusion differ in various studies.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with pleural involvement have poor clinical outcomes (24)(25)(26)(27). Our study revealed that pleural involvement is an independent prognostic factor for PFS and OS in both patients with pulmonary B-cell NHLs and the PPL subgroup.…”
Section: Discussionmentioning
confidence: 62%
“…Although malignancy is a rare cause, pleural effusion may be seen at diagnosis in 15% of children with non-Hodgkin lymphoma and is a marker for poor therapeutic response and relapse. Suggested causes include venous obstruction from bulky disease, leading to a decreased venous return to the heart and reduced lymphatic drainage of the thoracic duct if the left brachiocephalic vein is involved [45]. Pleural effusions are readily demonstrated on chest radiography and pleural ultrasound, with the latter able to assess the complexity, and approximate size of the effusion.…”
Section: Intra-thoracic Emergenciesmentioning
confidence: 99%